Implementation of Learning History in The Merdeka Curriculum at Vocational School and SMA Muhammadiyah Palu City - Wildasari; Windayanti; Suyuti; Iskandar (Kirana Publisher (KNPub), 2025)
This research discusses the planning, implementation and evaluation of history learning in the independent curriculum in SMK and SMA Muhammadiyah Palu City. This study aims to find out how to plan, implement, and evaluate history learning in the independent curriculum in SMK and SMA Muhammadiyah in Palu City. The method used is qualitative that produces descriptive data with data collection through observation, interviews, and documentation. The results showed that; 1) Learning Planning History has been carried out well according to the principle of an independent curriculum, marked by the preparation of teaching modules, learning achievements, objectives, and teacher training that provides flexibility to adjust learning with student interests and needs; 2) The implementation of learning goes well by applying different stages and strengthening the profile of Pancasila students in contextual and collaborative manner; 3) Evaluation is carried out using formative and summative assessments with flexible methods. Although there are obstacles such as low student interests and lack of teacher training, this is overcome through interactive and independent learning methods. This study confirms the need for a more in -depth study related to the strategy of overcoming obstacles and their impact on increasing student learning outcomes in a sustainable manner .